Molecular and biochemical mechanisms of mitochondrial dysfunction in spontaneously hypertensive rats on the background of carvedilol and thiotriazoline usage - Nahorna, E. A.; Chekman, I. S.; Belenichev, I. F.; Kolesnik, Yu. M.; Abramov, A. V.; Gorchakova, N. A.; Levich, S. V.; Нагорна, О. А.; Чекман, І. С.; Бєленічев, Ігор Федорович; Колесник, Юрій Михайлович; Абрамов, Андрій Володимирович; et al. (Hikari Ltd, 2016)
Objective: In conditions of hypertension, ATP synthesis can be violated that can lead to the development of energy deficit of cardiomyocytes. One of the reasons of such energy deficit could be mitochondrial dysfunction. Aim of this work was study of molecular and biochemical mechanisms of mitochondrial dysfunction in spontaneously hypertensive rats. Materials and Methods: Experiment was carried out on normotensive albino male rats and spontaneously hypertensive male rats. Animals were kept in the vivarium during 20 days. On Day 20 of the experiment we measured blood pressure of rats by plethysmography. In the myocardium of normotensive rats and animals with spontaneous hypertension we defined the degree of opening of mitochondrial oscula, the content of adenine nucleotides in the mitochondrial and cytosolic fractions of rat myocardium and energy metabolism parameters (energy charge, energy potential, phosphorylation rate and thermodynamic breath control).
Keywords: hypertension; heat shock proteins; mitochondrial dysfunction